The Hegemony of Social, Cultural, and Discourse Power Indonesian Language Literary Criticism Course Materials - Amien Denis, Muhammad; Gomo Attas, Siti; Anwar, Miftahulkhairah (International Journal of Education and Digital Learning (IJEDL), 2023)
One class dominates or is supported across numerous social aspects in hegemony. This study used critical discourse analysis to analyze data. This research aimed to analyze social hegemony in Indonesian literary criticism course materials. Thus, this study formulated problems as follows. (1) Social hegemony in Indonesian literary criticism course materials. (2) Persuasive cultural hegemony in Indonesian literary criticism course materials (3) Power hegemony in Indonesian literary criticism textbooks. In Indonesian literary criticism course materials, discursive practices, social identity, and social interaction are dialectical. Literary discourse is examined from three angles: the text, discourse practices, and the socio-cultural setting. Literary discourse as a manifestation of social interaction, its ability to regulate or manipulate behavior and material existence, and its role in establishing and maintaining power, status, and social roles are examined in the context of social hegemony. Critical examination of literary discourse in Indonesian literary criticism course materials is possible by considering cultural hegemony. According to the first assumption, symbols create meaning. b) Indonesian literary criticism textbooks link knowledge to values. Indonesian literary criticism course materials include cultural discourse from several fields. The hegemony of power is examined in Indonesian literary criticism course materials. a) Authority affects daily life. Power is coercive. Indonesian literary criticism course materials allow readers to criticize and disrupt social, cultural, and authority systems through literary discourse.